Skrining Fitokimia dan Uji Aktivitas Antibakteri Fraksi Etil Asetat dan n-Heksana dari Daun Mangga Kasturi (Mangifera casturi Kosterm.): Antibacterial Activity Test of Ethyl Acetate and n-Hexane Fraction from Kasturi Mango Leaves (Mangifera casturi Kosterm.) - Dwi Lestari; Desy Fitriani; Serli Anngraeni (KOVALEN: Jurnal Riset Kimia, 2021)
Kasturi mango (Mangifera casturi Kosterm.) is a typical mango of South Kalimantan. Kasturi mango leaves are reported to have antioxidant activity and are potential for treating various diseases, including diseases related to antibacterial. This study examines the antibacterial activity of ethyl acetate fraction and the n-hexane fraction of mango musk leaves on bacteria that cause acne. Experimental research started with plant determination, making extracts and fractions, phytochemical screening, and antibacterial testing against Staphylococcus aureus and Propionibacterium acnes using the disk diffusion method. The study results found that the ethyl acetate and n-hexane fractions had weak antibacterial activity against S. aureus and P. acnes bacteria, which cause acne